Identifying and Ranking Core Elements of Counseling-Based Interventions that Enhance Student Self-Belief and Motivation - Hoxha, Ardit; Bennis, Fatima (KMAN Counseling & Psychology Nexus, 2026)
The objective of this study was to identify and rank the core elements of counseling-based interventions that effectively enhance student self-belief and academic motivation. This study employed a sequential exploratory mixed-methods design. In the qualitative phase, an extensive literature review was conducted until theoretical saturation was reached, and findings were analyzed using NVivo 14 to identify core components of counseling-based interventions. Seven main themes were extracted and used to construct the quantitative instrument. In the quantitative phase, a structured survey was administered to 260 university students in Morocco, who rated each identified element on a five-point Likert scale. Descriptive statistics and ranking analyses were conducted using SPSS-26 to determine the relative importance of each intervention component. Statistical analysis revealed significant differences in the perceived importance of counseling components, with cognitive empowerment strategies receiving the highest mean ranking (M = 4.70), followed by emotional regulation and support (M = 4.60), behavioral activation (M = 4.50), and supportive counseling relationship (M = 4.30). Social and environmental influences demonstrated moderate importance (M = 4.10), while identity and self-concept development (M = 3.90) and intervention structure and delivery quality (M = 3.80) ranked lower but remained positively evaluated. The ascending ranking pattern indicated that internal psychological processes were prioritized above structural or contextual supports. The study concludes that cognitive and emotional components form the strongest foundation for effective counseling-based interventions aimed at enhancing student motivation and self-belief, while relational, social, identity-related, and structural elements play complementary but essential supporting roles. The results provide a practical, evidence-based hierarchy to guide the development and refinement of counseling programs in educational settings.